The Fiscal Multiplier of European Structural Investment Funds : Aggregate and Sectoral Effects with an Application to Slovenia. (IMF Working Papers; Working Paper ;, 2021)
In this paper, we estimate the aggregate and sectoral fiscal multipliers of EU Structural Investment (ESI) Funds and of public investment at the EU level. We complement these results with a specific application to the case of Slovenia. We first analyze aggregate data and find large and significant multipliers and strong crowding-in of private investment. Our main findings show that positive shocks to ESI Funds are followed by an increase in output that ranges from 1.2 percent on impact, to 1.8 percent after 1 year, and by an increase in private investment between 0.7 and 0.8 percent of GDP. We address country heterogeneity by dividing countries according to key characteristics that have been known to affect multipliers. In particular, we find higher multipliers in a group of CEE countries that are important recipients of European funds and are characterized by fixed exchange rate regimes and sound public investment governance (e.g. Croatia and Slovenia). We also complement the aggregate analysis by estimating the effect of different types of public investment and the effect of public investment on different sectors of the economy.